RF CMOS transceiver at 2.4 GHz in wearables for measuring the cardio-respiratory function - Carmo, João Paulo Pereira (2011)
This paper presents a radio-frequency (RF) transceiver for operation in the 2.4 GHz ISM band. The RF CMOS transceiver can be supplied with only 1.8 V, and it was designed to establish wireless links for distances up to 10 m, for a maximum baud-rate of 250 Kbps with a Bit Error Probability less than 10 6. The transmitter can deliver a output power of 0 dBm with a consumption of only 11.2 mW, while the receiver has sensitivity of 60 dBm and consumes only 6.3 mW. The goal of RF CMOS transceiver is for co-integration with sensors in the same die using microsystems techniques. The target application of such microsystems is in wearables (e.g., in wireless electronic shirts) for measuring biomedical data of patients. The wireless electronic shirt (WES) measures the heart rate and the respiratory frequency, and at the same time it allows patients to maintain their mobility